Aktywność w czasie wolnym młodzieży studiującej - Słupska, Kamila (Kultura-Społeczeństwo-Edukacja, 2018)
The article refers to students’ free time. It includes: theoretical explanations concerning the essence and meaning of the main above-mentioned category, review of the outcomes of a research conducted on free time activities of the studying youth, and – as an illustration to these considerations – a report from a personal research. As a part of it, the respondents referred to, among others, the significance of free time in life, its functions, ways of making use of it (actual ones and the ones longed for), and factors contributing to it.